A família Asteraceae na Serra Geral de Licínio de Almeida, Bahia, Brasil - Santana, Fernanda Afonso (2013)
Serra Geral de Licínio de Almeida (SGLA) is located in the central portion of the Espinhaço range, a region with no floristic studies. This paper presents the inventory of Asteraceae for the SGLA. Samples were collected in six bimonthly field trips (2011-2012) and the collected materials are inserted at HUEFS Herbarium. The results are presented in the checklist of the species, keys to tribes and species, followed by comments, aspects of reproductive phenology and geographical distribution of each species. Eighty-three species and 38 genera were found, represented in 12 tribes of Asteraceae. Of these, 13 are new records for Bahia state (Aldama oblongifolia, Aldama bracteata, Aspilia eglerii, Aspilia floribunda, Dasyphyllum vagans, Eremanthus polycephalus, Gochnatia discolor, Lychnophora ramosissima, Lepidaploa barbata, Lessingianthus laevigatus, Lessingianthus psilophyllus, Mikania obtusata e Proteopsis argentea) and two are new species to science (Lychnophora sp. 1 and Anteremanthus sp. nov.). The most representative tribe was Vernonieae (36 spp.), followed by Eupatorieae (17 spp.) and Heliantheae (8 spp.). The genera with the largest number of species were Lessingianthus (eight spp.), followed by Lepidaploa, Vernonanthura and Gochnatia, with five species each. A map of the study area with the respective collection sites and unpublished illustrations of Agrianthus myrtoides, Aspilia floribunda, Anteremanthus sp. nov., Chresta harleyi, Gochnatia densicephala, Lychnophora sp. 1 and Stomatanthes polycephalus are included as part of the results.